(untitled) (The Conference Hub, 2025)
This article analyzes the views of Muhammad Abduh, a prominent Islamic thinker who lived and worked at the turn of the nineteenth and twentieth centuries, regarding the educational system of the Ottoman Empire. It examines the activities of traditional religious educational institutions—madrasas and schools—operating during the Ottoman period, their role in socio-political life, and the content of education. The study highlights Abduh’s reformist approach to education and his efforts to harmonize religious and secular sciences.